Assessment of toxicity and differential antimicrobial activity of methanol extract of rhizome of Simaba ferruginea A. St.-Hil. and its isolate canthin-6-one. (15th September 2018) - Gazoni, Vanessa Fátima; Balogun, Sikiru Olaitan; Arunachalam, Karuppusamy; Oliveira, Darley Maria; Filho, Valdir Cechinel; Lima, Samara Rosolem; Colodel, Edson Moleta; Soares, Ilsamar Mendes; Ascêncio, Sérgio Donizeti; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Simaba ferruginea A. St.-Hil., Simaroubaceae, popularly known as "calunga" is a typical subtropical shrub used in Central Brazil mainly for infection, anti-inflammatory, analgesic and gastric duodenal-ulcers. It presents in its composition the alkaloid canthin-6-one, an alkaloid indole β-carboxylic. Aim: This study aims to investigate the toxicity, antimicrobial activities of methanol extract of Simaba ferruginea (MESf) and canthin-6-one by using different experimental models. Methods: The present study evaluated the phytochemical analysis by high performance liquid chromatography (HPLC), toxicological potential of MESf and canthin-6-one, using the cytotoxicity, genotoxicity assays with CHO-K1 cells and in vivo acute test in mice. Antimicrobial activity was evaluated by the broth microdilution assays, while the antimicrobial mechanism of action was also assessed using different in vitro bacterial and fungal models. Results: The HPLC analysis of MESf revealed the presence of canthin-6-one, kaempferol and morin. Differential in vitro toxicities were observed between MESf and canthin-6-one. In the cytotoxicity assay, MESf presented toxicity against CHO-K1, while canthin-6-one did not. In the case of in vitro genotoxicity, both showed to be potentially genotoxic. In the in vivo toxicity study, both MESf (up to 1000 mg/kg) and cantin-6-one (up to 100 mg/kg) caused no toxicologically relevant alterations and are thus considered not to be toxic. MESf was shown to be relatively safe with NOAEL (100 mg/kg) when administrate in mice. Both MESf and canthin-6-one also showed differential antimicrobial activities. On one hand, MESf demonstrated good spectrum of antibacterial action against Staphylococcus aureus (MIC 12.5 μg/mL) and Escherichia coli (MIC 25 μg/mL) and moderate activity against Enterococcus faecalis and Shigella flexneri (MIC 200 μg/mL) but no antifungal effect. On the hand, canthin-6-one showed no antibacterial activity, except against Staphylococcus aureus (100 μg/mL), but potent in vitro fungicidal activity against clinically important Aspergillus niger and Candida species at MFC intervals ranging from 3.12 to 25 μg/mL. Both MESf and canthin-6-one were bacteriostatic in action. MESf antimicrobial mechanism of actions are associated with changes in the permeability of bacterial membranes, evidenced by the increased entry of hydrophobic antibiotic in Shigella flexneri, intense K + efflux ( Shigella flexneri, Staphylococcus aureus ) and nucleotides leakage ( Staphylococcus aureus ). In the antifungal mode of action, canthin-6-one inhibited Saccharomyces cerevisiae growth and including alteration in the cell membrane of Neurospora crassa . Conclusion: The results of this work demonstrated the differential antimicrobial activities of MESf and its alkaloid isolate, canthin-6-one with antibacterial and antifungal activities, respectively. The present study support the popular use of Simaba ferruginea in combatting afflictions related to bacterial infections, and demonstrate that canthin-6-one as a promising antifungal agent. Both MESf and canthin-6-one are considered non-toxic based on the in vitro toxicological study. Graphical abstract: